Persistent Urethritis and Prostatitis Due to Trichomonas vaginalis: A Case Report - Alireza Abdolrasouli; Abolghasem Amin; Manouchehr Baharsefat; Azita Roushan; Shamseddin Mofidi (Canadian Journal of Infectious Diseases and Medical Microbiology)
The present report describes a case of persistent urethritis accompanied by prostatitis due to Trichomonas vaginalis in a young male patient. The importance of the laboratory diagnosis of trichomoniasis in persistent or recurrent urethritis (ie, testing samples from multiple sites) is highlighted, with the aim of improving the clinical recognition of this pathogen.